The Presence of Glycogen Synthase in Preparations of Platelet Plasma Membranes - Greenberg, J. H; Fletcher, A. P; Jamieson, G. A (Thrombosis and Haemostasis, 1973)
Glycogen synthase and glycogen (63 ± 35 μg/unit) have been identified in partially-purified preparations of platelet membranes isolated by density-step centrifugation following glycerol-lysis; this combination is responsible for the endogenous (collagen-independent) activity measured during the assay of collagen: glucosyltransferase. Glycogen synthesized in this way may be complexed with protein since it is precip-itable with trichloracetic acid. High and low density membranes prepared by continuous density gradient centrifugation are devoid of glycogen synthase activity.